Pengaruh Kualitas Pelayanan, Harga, Promosi dan Customer Experience terhadap Loyalitas Pengguna ShopeeFood - Jesslyn Tendatio; Hanny Siagian; Tya Wildana Hapsari Lubis (Fakultas Bisnis Universitas Mikroskil, 2023)
The phenomenon of this research is the use of ShopeeFood among students since the Covid-19 pandemic. This study aims to determine and analyze the influence of service quality, price, promotion and customer experience on ShopeeFood user loyalty in Study Program of Management Business Faculty Mikroskil University Students. The sampling technique in this study was stratified random sampling with the type of research was quantitative descriptive. The population of this study were 207 students in year study 2019-2022 who had used ShopeeFood and 136 students as samples. The data analysis method is multiple linear regression with statistical hypothesis testing. The results showed that partially, service quality, price and promotion had positive and significant effect on user loyalty. Meanwhile, the customer experience has no effect on user. Furthermore, the simultaneous results, show that service quality, price, promotion and customer experience have an influence on user loyalty. Adjusted R2 shows that the variable service quality, price, promotion and customer experience can explain the user loyalty variable of 71.3% while the remaining 28.7% is influenced by other variables not examined in this study.